LaCoO3 perovskite oxide activation of peroxymonosulfate for aqueous 2-phenyl-5-sulfobenzimidazole degradation: Effect of synthetic method and the reaction mechanism - Pang, Xintong; Guo, Yang; Zhang, Yuting; Xu, Bingbing; Qi, Fei (Chemical engineering journal (Lausanne, Switzerland : 1996), 2016)
•The high efficiency LaCoO3 perovskite oxides were fabricated with three methods.•Heterogeneous reaction led to LCO-SiO2 activating PMS to form absolute SO4−.•LCO and LCO-CTAB showed combination of homogeneous and heterogeneous reactions.•Intermediates identification confirmed the radical reaction pathway. The degradations of aqueous solutions of 2-phenyl-5-sulfobenzimidazole acid (PBSA) using peroxymonosulfate (PMS) activated with LaCoO3 (LCO)-based perovskite oxides prepared by three different methods (including normal precipitate method named as LCO, introduction of cetyltrimethyl ammonium bromide (CTAB) named as LCO-CTAB and hydrothermal method with the adding of silicon named as LCO-SiO2) were investigated. The results showed that all the catalysts effectively degraded PBSA. At neutral pH, a removal efficiency of about 100% was achieved in less than 10min. LCO-SiO2 showed the widest solution pH range (4.0–8.0) with a lowest leaching of cobalt and lanthanum ions (both less than 5.0%). The surface and structural properties of the catalysts were determined using X-ray diffraction, N2 adsorption–desorption, transmission electron microscopy, and X-ray photoelectron spectroscopy. The reaction involved LCO and LCO-CTAB was a combination reaction including homogeneous and heterogeneous reactions. The first one was caused by the leached cobalt ions; the later one was derived by the surface cobalt-oxygen bond. In the process of LCO-SiO2 activated PMS, the heterogeneous activation reaction dominated PBSA degradation, which was derived by SO4− and electronic transfer confirmed by the effect of radical quenchers and intermediates identification. Eight intermediates generated from PBSA degradation were identified using gas chromatography–mass spectrometry. The identification of HO3SO− among the products confirmed the proposed SO4− degradation mechanism.